Comparison of in situ and peripheral host immunity to syngeneic tumours employing the multicellular spheroid model. - Lord, E. M. (Nature Publishing Group, 1980)
The multicellular tumour spheroid was used as a model system to assess the in situ host immune response to the EMT6/Ro mammary tumour in syngeneic BALB/cKa mice. In sensitized mice the spheroids were rapidly infiltrated by host cells including macrophages, lymphocytes and granulocytes. Tumour cell killing was evident within 1 day and resulted in the eventual complete destruction of the spheroids. Host cells within the spheroids had a greater cytolytic capacity than the surrounding peritoneal cells and virtually no cytolytic activity was detectable in cells from the spleen. A similar discrepancy between in situ and peripheral immunity was found in mice bearing solid EMT6/Ro tumours.